2023
DOI: 10.1038/s41541-023-00731-w
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional CD4 T-cells correlating with neutralising antibody is a hallmark of COVISHIELDTM and COVAXIN® induced immunity in COVID-19 exposed Indians

Srabanti Rakshit,
Sudhir Babji,
Chaitra Parthiban
et al.

Abstract: Detailed characterisation of immune responses induced by COVID-19 vaccines rolled out in India: COVISHIELDTM (CS) and COVAXIN® (CO) in a pre-exposed population is only recently being discovered. We addressed this issue in subjects who received their primary series of vaccination between November 2021 and January 2022. Both vaccines are capable of strongly boosting Wuhan Spike-specific neutralising antibody, polyfunctional Th1 cytokine producing CD4+ T-cells and single IFN-γ + CD8+ T-cells. Consistent with inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…Of note, the T-cell responses to the two vaccines in the SJRI cohort which comprised mostly of COVID-19 exposed individuals, differed in magnitude when they were segregated based on their baseline nucleocapsid titres. 14 This is consistent with studies on mRNA vaccines in seropositive subjects where a single dose induced a rapid increase in antibody titers. 18 , 19 The negative role of high levels of circulating antibodies on vaccine immunogenicity and/or efficacy has also been observed with other vaccines.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Of note, the T-cell responses to the two vaccines in the SJRI cohort which comprised mostly of COVID-19 exposed individuals, differed in magnitude when they were segregated based on their baseline nucleocapsid titres. 14 This is consistent with studies on mRNA vaccines in seropositive subjects where a single dose induced a rapid increase in antibody titers. 18 , 19 The negative role of high levels of circulating antibodies on vaccine immunogenicity and/or efficacy has also been observed with other vaccines.…”
Section: Discussionsupporting
confidence: 87%
“…The fourth cohort (SJRI), in which the vaccination overlapped with the omicron wave, showed comparable post-vaccination antibody titres in the Covishield™ and Covaxin® recipients. 14 However, antibody titres in this fourth cohort with delayed recruitment confirmed that the waning of the immune response was slower in Covishield™ recipients. 14 Importantly, we also confirmed these findings using an independent assay platform, the MSD platform which has a higher dynamic range.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Additionally, vaccination has been found to reinforce protection against the Wuhan strain infection. Indeed, the initial vaccines were developed from this strain [30]. In line with these observations, our results indicate that vaccinated groups exhibited the strongest response against strain W in Madagascar and CAR (Figure 3a).…”
Section: Discussionsupporting
confidence: 85%
“…T-cell polyfunctionality has been identified in both the CD4+ and CD8+ subsets, with the cells being capable of secreting combinations of cytokines. The presence of polyfunctional T-cells of both the CD4+ and CD8+ subsets was linked with the protective effect of anti-SARS-CoV-2 vaccines on humans [ 68 , 69 ], through the production of interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), and interleukin-2 (IL-2) [ 70 ]. Since the analysis of single cytokines produced by the T-cells of mice immunized with our HBc/G161-CTL and HBc/G175-CTL proteins did not reveal a statistically significant response after stimulation with the mixed SARS-CoV-2 CTL peptides, we performed a combined test for the population of cells expressing three cytokines—IFN-γ, IL-2, and TNF-α—when stimulated by a pooled sample of the five CTL peptides used in this study.…”
Section: Discussionmentioning
confidence: 99%